(untitled) - Bailey, R. (Rosemary) (Cambridge,New York, 2004)
Rosemary Bailey covers in this study the mathematics of association schemes--an area lying between pure mathematics and statistics that relates to the optimal design of scientific experiments. The book is accessible to mathematicians as well as statisticians. Arising from a graduate course taught by the author, it appeals to students as well as researchers as a valuable reference work from which to learn about the statistical/combinatorial aspects of their work.
Keywords: Association schemes (Combinatorial analysis),Experimental design,Giải tích tổ hợp,Thiết kế thí nghiệm